2018
DOI: 10.1093/jme/tjy032
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding Reveals Hidden Diversity of Sand Flies (Diptera: Psychodidae) at Fine and Broad Spatial Scales in Brazilian Endemic Regions for Leishmaniasis

Abstract: Sand fly (Diptera: Psychodidae) taxonomy is complex and time-consuming, which hampers epidemiological efforts directed toward controlling leishmaniasis in endemic regions such as northeastern Brazil. Here, we used a fragment of the mitochondrial cytochrome c oxidase I (COI) gene to identify sand fly species in Maranhão State (northeastern Brazil) and to assess cryptic diversity occurring at different spatial scales. For this, we obtained 148 COI sequences of 15 sand fly species (10 genera) from Maranhão (fine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 57 publications
2
38
0
1
Order By: Relevance
“…The combined set of sequences was then aligned using MUSCLE (Edgar, 2004) implemented in MEGA version 7 (Kumar et al, 2016). As our data set included sequences of varying length, we constructed two alignments: (a) a 658 bp alignment covering the full-length of the amplicon generated by the Folmer et al (1994) primers, which contained some missing data at the 5 ′ and/or 3 ′ termini of some of the sequences, and (b) a cropped, partial 543 bp version of the former alignment, corresponding to the region analysed by Rodrigues et al (2018), and which contained no missing data. The full-length 658 bp alignment was used for the phylogenetic analyses reported here, with partial sequences appropriately coded as having missing data.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The combined set of sequences was then aligned using MUSCLE (Edgar, 2004) implemented in MEGA version 7 (Kumar et al, 2016). As our data set included sequences of varying length, we constructed two alignments: (a) a 658 bp alignment covering the full-length of the amplicon generated by the Folmer et al (1994) primers, which contained some missing data at the 5 ′ and/or 3 ′ termini of some of the sequences, and (b) a cropped, partial 543 bp version of the former alignment, corresponding to the region analysed by Rodrigues et al (2018), and which contained no missing data. The full-length 658 bp alignment was used for the phylogenetic analyses reported here, with partial sequences appropriately coded as having missing data.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…lenti (Mangabeira, 1938) -are not readily distinguishable from one another using standard methodology (i.e. distance-based neighbour-joining clustering) applied to the Folmer et al (1994) coi barcoding region (Pinto et al, 2015;Rodrigues et al, 2018), despite clear and distinct morphological differences existing between these three species (such as the shapes of paramere and the apex of the aedeagal ducts of males, and the shape of the spermathecae in females; Galati, 2018). In contrast, the three other barcoded morphospecies of this subgenus -E.…”
Section: Introductionmentioning
confidence: 99%
“…longipalpis complex specimens from Honduras, Venezuela, Colombia, Brazil, Paraguay and Argentina. (7,28) Studies carried out by Pinto et al (15) and Rodrigues et al (16) on molecular taxonomic identification, supported the possibility of introgression events between Lu. longipalpis complex and both Lu.…”
Section: Discussionmentioning
confidence: 79%
“…Mitochondrial DNA (mtDNA) markers, as COI gene, have been used for phylogenetic relationships inference, phylogeography, population genetics and molecular taxonomic identification (DNA barcoding) in phlebotomine sand flies from the new and old world. 15 , 16 , 17 , 18 , 19 Given the medical importance of some phlebotomine sand flies within Nyssomyia genus and Lutzomyia subgenus, the studies of phylogenetic relationships will increase our understanding of the evolutionary relationships within these closely-related species, which to date has not yet been explored. Gene flow between these phlebotomine sand flies may influence vector competence and capacity and could have important epidemiological consequences such as insecticide resistance or susceptibility to Leishmania infection.…”
mentioning
confidence: 99%
“…A fragment of the cytochrome c oxidase subunit I ( COI ) mitochondrial gene has been widely used in molecular taxonomy to resolve these kinds of issues 8 . Even if several studies have employed COI barcode sequences to identify Phlebotominae species and revealed species complexes in America, 9 , 10 , 11 (among others) its use can be problematic in closely related species because of incomplete lineage sorting and introgression events 12 . The strategies designed to delimit species boundaries have been developed, among them is clustering, which does not require a priori definitions of species 13 .…”
mentioning
confidence: 99%